Financial Education for children: Playing with money - Albuquerque Ventura, Ana Flávia; de Almeida Abrantes, Taynar Ingrid; Costa Ferreira, Ingrid Renally; Costa dos Santos, Raissa; Ventura Júnior, Raul (Guará Journal, 2018)
This paper aims to demonstrate the effectiveness of financial education for children in order to make users easier to deal with credit alternatives in the market and become more conscious consumers. For this, they buy activities with children from elementary school, precisely from the 2nd to the 5th year of public and private schools in the city of Sousa in Paraíba, with 444 students. An idea was divided as activities to be exercised according to each series, obtaining a greater income of the students in relation to the content addressed, since the activity of the company is proportional to the degree of learning, with a view to thinking about the possibility of incorporating into the curriculum from schools as contributions brought by research. This perspective sees children as being able to understand as appropriate skills to take care of their own resources and thus become independent as quickly as possible. Thus, after the implementation of the activities, we find out what results are obtained, how successful are the goals-initiatives and that all parties involved in the process are satisfied. This debate is a debate about the preliminary publications, considering the possibilities of debate and the dissemination of an information base considering an object of knowledge as relevant content to be developed in the classroom. The relevance of the project is an effective enough awareness to show how all people a real importance of Child Financial Education.